Kewirausahaan Bagi Penyandang Disabilitas dalam Angkatan Kerja: Peluang dan Tantangan - Debataraja, Juliana; Rahmahtrisilvia, Rahmahtrisilvia (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study is to systematically examine the development of entrepreneurship studies among people with disabilities by analysing the available opportunities and structural barriers that affect the success of independent businesses. This study uses a systematic literature review method by analysing 25 reputable scientific articles published between 2007 and 2025 and obtained from major academic databases using keywords related to disability entrepreneurship, barriers, and supporting factors. The selected articles were analysed and grouped thematically into three main aspects, namely entrepreneurial opportunities, systemic barriers, and supporting factors at the ecosystem level. The results of the study show that entrepreneurship has significant potential as a means of increasing the economic independence, autonomy, and self-confidence of persons with disabilities. However, this potential is still limited by restricted access to capital, low availability of inclusive entrepreneurship training, and persistent social stigma and discrimination. The findings also show that the success of entrepreneurship among persons with disabilities is more influenced by environmental, institutional, and public policy factors than by individual characteristics alone. Therefore, this study emphasises the importance of inclusive policies, strengthening a disability-friendly entrepreneurial ecosystem, and providing continuous support to encourage equal economic participation.